2017
DOI: 10.1007/s11033-017-4116-1
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the cyanobacterial lectin scytovirin: new insights into binding properties

Abstract: Scytovirin is a lectin isolated from the cyanobacterium Scytonema varium that has shown activity against HIV, SARS coronavirus and Zaire Ebola virus. Its 95 amino acids are divided into two structural domains (SD), the first spanning amino acids 1-48 (SD1) and the second 49-95 (SD2). Interestingly, the domains are nearly identical but differ in their affinities for carbohydrates. With the aim of enhancing understanding of the binding properties of scytovirin, we performed molecular dynamics (MD) simulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…SVN binds to the Manα(1-2), Manα(1-6),Manα(1-6)Man tetrasaccharides of the viral enveloped glycoproteins, especially to gp120, but also gp160 and less effectively to gp41 [ 43 ]. The binding proceeds simultaneously at the two domains (SD1 and SD2), but domain SD1 has a higher affinity for oligosaccharides than SD2 [ 75 , 76 ]. The in silico studies showed that for the two domains the mechanism of the SVN–Man4 interactions was different [ 76 ].…”
Section: Cyanobacterial Lectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…SVN binds to the Manα(1-2), Manα(1-6),Manα(1-6)Man tetrasaccharides of the viral enveloped glycoproteins, especially to gp120, but also gp160 and less effectively to gp41 [ 43 ]. The binding proceeds simultaneously at the two domains (SD1 and SD2), but domain SD1 has a higher affinity for oligosaccharides than SD2 [ 75 , 76 ]. The in silico studies showed that for the two domains the mechanism of the SVN–Man4 interactions was different [ 76 ].…”
Section: Cyanobacterial Lectinsmentioning
confidence: 99%
“…The binding proceeds simultaneously at the two domains (SD1 and SD2), but domain SD1 has a higher affinity for oligosaccharides than SD2 [ 75 , 76 ]. The in silico studies showed that for the two domains the mechanism of the SVN–Man4 interactions was different [ 76 ].…”
Section: Cyanobacterial Lectinsmentioning
confidence: 99%
“…It increases insulin sensitivity thanks to the antioxidant effects of phycobiliproteins. So, interleukin 6 (IL-6), which inhibits insulin signaling molecules such as insulin receptor substrate, is regularized [ 141 , 142 , 143 ], and the activity of the lipoprotein lipase, an important enzyme in the lipid metabolism when it is altered in HIV patients, is increased [ 144 , 145 ].…”
Section: An Overview Of the Antiviral Effects Of A Supplementary Microalgae Diet And Its Possible Action On Sars-cov-2mentioning
confidence: 99%
“…The search for these new resources largely involves the biotechnology and bioprospecting of microorganisms that are not toxic to the environment in which they live and that present advantages in their production. The researches commonly involve interest for metabolites with biological activity and, for a high-potential of biomass which are produced by these microorganisms, making them an alternative raw material to existing ones [ 1 , 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for inputs, it is well known that the marine environment is abundant in organisms that produce substances with high biotechnological value; enable a wide variety of products and which can be used as possible solutions to diseases due to the discovery of new substances with biological activity. Therefore, there is a great demand for different species of marine cyanobacteria and microalgae which may have unknown substances or untapped actions with pharmacological potential [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%